2016
DOI: 10.1007/s10802-016-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Symptom Dimensions Demonstrate Unique Relationships with the Startle Reflex in Anticipation of Unpredictable Threat in 8 to 14 Year-Old Girls

Abstract: There is growing evidence that heightened sensitivity to unpredictability is a core mechanism of anxiety disorders. In adults, multiple anxiety disorders have been associated with a heightened startle reflex in anticipation of unpredictable threat. Child and adolescent anxiety has been linked to an increased startle reflex across baseline, safety, and threat conditions. However, it is unclear whether anxiety in youth is related to the startle reflex as a function of threat predictability. In a sample of 90 8 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 118 publications
(149 reference statements)
1
14
3
Order By: Relevance
“…The NPU‐threat task has been employed using a variety of aversive stimuli, including shocks (Bradford, Shapiro, & Curtin, ; Grillon et al, ; Nelson & Shankman, ; Shankman et al, ), noises (Nelson & Hajcak, ; Schmitz et al, ), air blasts (Chamberlain et al, ; Grillon et al, ), and a breathing occlusion (Schroijen et al, ). In one of the few investigations that included multiple aversive stimuli, Grillon and colleagues (2004) used a between‐subjects design to examine the startle reflex in anticipation of predictable and unpredictable air blasts and shocks.…”
Section: Introductionmentioning
confidence: 99%
“…The NPU‐threat task has been employed using a variety of aversive stimuli, including shocks (Bradford, Shapiro, & Curtin, ; Grillon et al, ; Nelson & Shankman, ; Shankman et al, ), noises (Nelson & Hajcak, ; Schmitz et al, ), air blasts (Chamberlain et al, ; Grillon et al, ), and a breathing occlusion (Schroijen et al, ). In one of the few investigations that included multiple aversive stimuli, Grillon and colleagues (2004) used a between‐subjects design to examine the startle reflex in anticipation of predictable and unpredictable air blasts and shocks.…”
Section: Introductionmentioning
confidence: 99%
“…One potentially important, yet unaddressed consideration that may contribute to the variable results across studies is that the underlying relationships between psychophysiological responding and core elements of psychiatric disorders might be obscured by categorical diagnoses ( 45 , 46 ). This could be especially relevant to BPD which has a complex, polythetic presentation, with notable individual differences in BPD symptom severity among individuals who meet diagnostic criteria for BPD, as well as among individuals in the general population, albeit at sub-diagnostic levels ( 47 , 48 ).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty is known to elicit subjective distress (even in healthy individuals). This anxious apprehension is exaggerated in clinical populations ( 52 55 ) and may have maladaptive downstream consequences, including behavioral avoidance ( 53 ). Work in youth samples has suggested that the potentiating effects of uncertainty on threat responding are present across development ( 55 57 ).…”
mentioning
confidence: 99%
“…This anxious apprehension is exaggerated in clinical populations ( 52 55 ) and may have maladaptive downstream consequences, including behavioral avoidance ( 53 ). Work in youth samples has suggested that the potentiating effects of uncertainty on threat responding are present across development ( 55 57 ). Neuroimaging work on threat predictability—conducted primarily in adults—demonstrates involvement of threat circuitry, including the amygdala and thalamus, during various aspects of unpredictable threat anticipation and response ( 58 61 ).…”
mentioning
confidence: 99%